Estimate of the Internet banking user security - Антипов, И.Е.; Бочаров, Б.В.; Найденова, Д.Р. (Radiotekhnika, 2020)
The paper deals with security threats in the popular Internet banking service, the spread of which is becoming more common. Threats to the Internet banking users related to the use of telecommunication networks and means of communication are summarized and analyzed. Four main vulnerabilities have been identified: phone theft, social engineering methods, interception of data transmitted or stored on a mobile device, theft of SIM card data. Methods for numerically assessing the vulnerability of an Internet banking user due to these threats have been proposed. They are based on expert assessment method. The obtained numerical estimates will make it possible to use the existing methods for calculating risk. It is shown that currently the greatest threat is posed by methods of social engineering. A set of measures is proposed for users to counter the considered threats and a methodology for assessing their effectiveness, based on the expert assessment method too. It is shown that the most effective measure is the use of a separate telephone for Internet banking without an operating system. The proposed methods can be used to assess the effectiveness of any other measures to improve the security level of Internet banking users from threats associated with the use of telecommunication networks and communications. This method can be refined and adjusted to other information security objects or temporary changes in the field of information protection.